DIALECT POLITENESS: IS VIOLATING THE COOPERATIVE PRINCIPLE AN IMPOLITENESS? - Fahruddin; Herlina Usman; Sintowati Rini Utami (Getsempena English Education Journal, 2022)
The way someone shows politeness in speech acts is not only seen from a macro understanding of how speech participants can keep each other's face and maintain maxims with the inclusion of linguistic elements. Politeness of speech acts should be seen and understood on a micro level; more specifically in the context of language use in a language community as a cultural practice, both collectively and individually. Using the ethnographic perspective of communication, the current study investigates the politeness of speech acts in the context of guidance and counselling communication interactions in senior high schools, in the province of Southeast Sulawesi, Indonesia. The results of the analysis of S-P-E-A-K-I-N-G showed that the politeness of speech acts that appeared in the guidance and counselling process was mediated pragmatically by the use of local dialects. To find the forms, functions, strategies, and cooperative principles of speech act politeness that exist in the speech process, further analysis is carried out using coding techniques which also aims to construct a concept. The results of the analysis showed three forms of politeness, four functions of politeness, six strategies of politeness, and two principles of cooperative principles. The current study understands that violating the principle of cooperation in the context of communication in this study is actually a courtesy and that is why a polite speech act should be relied on the context in which a communication happened. This understanding was constructed theoretically then labelled as 'Dialect politeness' as a cultural communication practice.